Diffusion coefficients during osmotic dehydration of tomatoes in ternary solutions - Telis, VRN; Murari, RCBDL; Yamashita, F. (Elsevier B.V., 2004)
The apparent diffusion coefficients for sucrose, NaCl and water during osmotic dehydration of tomatoes in ternary solutions were determined. Long time experiments (up to 60 h) were carried out in order to determine equilibrium concentrations inside tomatoes, whereas short time experiments (up to 4 h) were performed to provide detailed information on kinetics of water loss and solids gain at the beginning of osmotic treatment. The mass transfer rates for water and solutes showed to be dependent of NaCl and sucrose concentrations in osmotic solution and simple regression models as functions of solutes concentration were determined for diffusion coefficients. Salt and sucrose diffusivities showed to be interdependent, with increasing NaCl concentration causing the enhancement of water loss, at the same time that higher sucrose contents hindered the excessive salt penetration. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: apparent diffusion coefficients; moisture loss; salt gain; sucrose gain